Contribution of Medicine Ball Throw, Bar Twist, and Lateral Bound Training on Increasing Results of O'brien Style Bullets in SMA Negeri 2 Athletic Boys in 2022 - Nono Hardinoto; Ega Ardiani (Journal Physical Education, Health and Recreation, 2021)
This study aimed to determine the jointly significant contribution of medicine ball throw, bar twist, and lateral bound exercises to the improvement of O'Brien style shot put results for male athletes at SMA Negeri 2 Kisaran in 2022. The research method used is an experimental method with a research design of one group pre-test and post-test design. The number of samples in this study amounted to 8 people. The research was conducted in the Field of SMA Negeri 2 Kisaran Nusantara VIII Kisaran, Asahan Regency. This study's statistical calculations are requirements analysis, normality, Bartlet test/homogeneity, and regression significance tests. From hypothesis testing, it can be concluded that there is a jointly significant contribution of medicine ball throw, bar twist, and lateral bound exercises to the improvement of the O'Brien style shot put for male athletes at SMA Negeri 2 Kisaran in 2022.